2020
DOI: 10.1136/archdischild-2020-319065
|View full text |Cite
|
Sign up to set email alerts
|

Add-on bone scintigraphy after negative radiological skeletal survey for the diagnosis of skeletal injury in children suspected of physical abuse: a systematic review and meta-analysis

Abstract: Objective(s)To systematically assess the extent to which bone scintigraphy (BS) could improve the detection rate of skeletal injury in children suspected of physical abuse with an initial negative radiological skeletal survey (RSS).Study designWe searched MEDLINE and Web of Science for series of ≥20 children suspected of physical abuse who underwent RSS and add-on BS. We assessed the risk of bias and the heterogeneity and performed random-effects meta-analyses.ResultsAfter screening 1140 unique search results,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…The guidelines were based on a limited number of well-designed primary studies, particularly for the definition and diagnosis of sentinel injuries, 14 , 50 the use of bone scintigraphy, 20 and laboratory tests 29 , 51 to perform in case of suspected CPA. The lack of primary studies may have led guidelines developers to opt for expert consensus rather than evidence-based guidelines, and this may explain the substantial heterogeneity among guidelines.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The guidelines were based on a limited number of well-designed primary studies, particularly for the definition and diagnosis of sentinel injuries, 14 , 50 the use of bone scintigraphy, 20 and laboratory tests 29 , 51 to perform in case of suspected CPA. The lack of primary studies may have led guidelines developers to opt for expert consensus rather than evidence-based guidelines, and this may explain the substantial heterogeneity among guidelines.…”
Section: Discussionmentioning
confidence: 99%
“… 55 , 56 , 57 , 58 , 59 Thus, an update of the oldest included guidelines would probably lead to more between-guideline consistency. Other systematic reviews have shown the complete lack of well-designed original studies, such as for bone scintigraphy, 20 pointing to the need to conduct such studies. There is also a clear need to define sentinel injuries, to agree not just on their location, size, patterns, and number but also on the term sentinel injury because it is not shared by all experts in the field of CPA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations